Reduced prospective motor control in 10-month-olds at risk for autism spectrum disorder - Ekberg, T.; Falck-Ytter, T.; Bölte, Sven; Gredebäck, G.; Campbell, L.; Cauvet, E.; Kleberg, J.; Jobs, E.; Nyström, P.; Thorup, E.; Zander, E. (Sage Publications, 2016)
Motor impairments are not a part of the diagnostic criteria for autism spectrum disorder (ASD) but are overrepresented in the ASD population. Deficits in prospective motor control have been demonstrated in adults and older children with ASD but have never before been examined in infants at familial risk for the disorder. We assessed the ability to prospectively control reach-to-grasp actions in 10-month-old siblings of children with ASD (high-risk group, n = 29, 13 female) as well as in a low-risk control group (n = 16, 8 female). The task was to catch a ball rolling on a curvilinear path off an inclined surface. The low-risk group performed predictive reaches when catching the ball, whereas the high-risk group started their movements reactively. The high-risk group started their reaches significantly later than the low-risk group (p = .03). These results indicate impaired prospective motor control in infants susceptible for ASD.